Development of Animation Learning Media Based on PBL to Improve Thematic Learning Outcomes Students - Lala Dyah Chandra; Pargito Pargito; Dwi Yulianti; Dina Maulina (IJORER : International Journal of Recent Educational Research, 2024)
Objective: 21st-century learning must prepare generations of Indonesian people to support information and communication technology advances in social life. The rapid development of technology in the current era of globalization provides multiple benefits for the world of education, so education requires students who play an active role and educators who create innovative learning. Learning innovation can be done in various ways, including developing interactive learning media. This aims to create exciting learning to improve students' thematic learning outcomes. Method: The research used Borg & Gall's research and development, creating an ecosystem into three stages in the VA and VB classes at 5 Way Serdang Public Elementary School. The sample consisted of 42 students in the experimental and control classes. The data analysis technique uses the Effect Size test. Results: The data obtained had an effect size of 1.02, with an extensive interpretation of the effect. Novelty: This research presents novelty by designing PBL-based animated learning media containing menus and moving images on the media to attract students' attention and enthusiasm. This aims to improve students' thematic learning outcomes.